Sternal Muscle: A Case Report - de Aguiar, Pamela Kelly Farias; Silva, Anna Caroline Duarte Costa; Oliveira, André de Sá Braga; Santos, Luciano Edgley dos; Gomes, Felippe Barbosa; Assis, Thiago de Oliveira (Journal of Morphological Sciences, 2019)
Introduction The sternal muscle is an anatomical variation found in the anterior region of the thorax.Objective To report the anatomical characteristics of a new type of sternal muscle.Case Report This was a dissection study in which the sternal muscle found was unilateral and long.Discussion Proximal fixation differs from the classification adopted for these cases. Documentation of sternal muscle variations can improve the theoretical database in anatomy as well as aid diagnoses, reducing the probability of the unexpected during clinical and/or surgical thorax-related investigations.
Keywords: sternal muscle; anatomical variation; clinical anatomy